PEREMPUAN SEBAGAI PELAKU DAN KORBAN KEKERASANDALAM KEHIDUPAN RUMAH TANGGADian Arlupi Utami dan Rr Nanik Setyowati Fakultas Ilmu Sosial, Universitas Negeri Surabaya (Lentera, Jurnal Studi Perempuan, 2013)
Abstract Woman is a unique figure.  Woman in household life is not  only as victims but  also perpetrators of violence as well as  household.  Women may commit acts of violence on children, husband is triggeredby a variety of family issuesfrom the trivial to severe levels. However,many cases were foundthat women are also victimsof violencethat can also beperformedby children or husbandsor other family members in their household. The issue of household violence affecting womenin both age children, adolescents and adults is what will be written sequentially in this article as a reference material, inputs forobservers ofthe socialproblems of women in particular cases. Recognize the characteristics of victims of violence, and implement appropriate remedial action type of abuse is needed. Cooperation of various parties such as family, community and government is needed so that women as victims and perpetrators of violence can be minimized. Keywords: Women, Perpetratorsand Victims, Household Violence